2021
DOI: 10.1111/cas.14761
|View full text |Cite
|
Sign up to set email alerts
|

α‐Emitting cancer therapy using 211At‐AAMT targeting LAT1

Abstract: α‐Methyl‐l‐tyrosine (AMT) has a high affinity for the cancer‐specific l‐type amino acid transporter 1 (LAT1). Therefore, we established an anti‐cancer therapy, with 211At‐labeled α‐methyl‐l‐tyrosine (211At‐AAMT) as a carrier of 211At into tumors. 211At‐AAMT had high affinity for LAT1, inhibited tumor cell growth, and induced DNA double‐stranded breaks in vitro. We evaluated the accumulation of 211At‐AAMT in vivo and the role of LAT1. Treatment with 0.4 MBq/mouse 211At‐AAMT inhibited tumor growth in the PANC‐1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 29 publications
0
30
1
Order By: Relevance
“…However, the therapeutic effect of 2- 211 At-AAMP was found to be insufficient, probably due to its low tumor retention. Other 211 At-labeled amino acids, including 211 At-labeled L-phenylalanine ( 211 At-Phe; Figure 1 c) and 211 At-labeled α-methyl-L-tyrosine ( 211 At-AAMT; Figure 1 a), have been successfully developed and have suppressed tumor growth in vivo [ 20 , 21 , 22 , 23 ]. However, there is concern about toxicity by irradiation following treatment with 211 At-Phe or 211 At-AAMT since they have shown a certain level of accumulation in normal organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the therapeutic effect of 2- 211 At-AAMP was found to be insufficient, probably due to its low tumor retention. Other 211 At-labeled amino acids, including 211 At-labeled L-phenylalanine ( 211 At-Phe; Figure 1 c) and 211 At-labeled α-methyl-L-tyrosine ( 211 At-AAMT; Figure 1 a), have been successfully developed and have suppressed tumor growth in vivo [ 20 , 21 , 22 , 23 ]. However, there is concern about toxicity by irradiation following treatment with 211 At-Phe or 211 At-AAMT since they have shown a certain level of accumulation in normal organs.…”
Section: Discussionmentioning
confidence: 99%
“…211 At-Phe was found to be taken up via not only LAT1 but also LAT2, which is expressed in normal organs [ 22 ]. 211 At-AAMT is a LAT1-specific radiopharmaceutical, but it showed high renal accumulation in the excretion process [ 23 ]. In addition, dehalogenation to release free 211 At was observed after the injection of 211 At-Phe and 211 At-AAMT, which can cause radiation exposure in the thyroid and stomach.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that 211 At caused more DSBs in a dose-dependent manner. Previously, we reported the dose-related induction of DSBs by 211 At-AAMT in PANC1 cells [15]. Alpha particles emitted from 211 At have higher LET than beta particles emitted from 131 I, and the severity and complexity of DNA damage signi cantly increase with alpha irradiation [16].…”
Section: Discussionmentioning
confidence: 99%
“…211 At, which can be produced in cyclotrons without the use of nuclear fuel material, emits high-energy α-rays with a relatively short half-life and can be clearly imaged by clinical scanners or autoradiography. 211 At has been recently labeled with various molecules including amino acid transporter substrates, inhibitors of prostate-specific membrane antigens, or antibodies against cancer-specific antigens for targeted alpha therapy of cancer via intravenous administration [ 18 20 ]. On the other hand, as far as we know, no treatments for antineoplastic tumors with 211 At-labeled AuNP have been reported so far.…”
Section: Introductionmentioning
confidence: 99%